Two new species of the family Noctuidae from China (Lepidoptera, Noctuidae) - Han, H.l.; Kononenko, V.s. (Zootaxa, 2017)
Two new species of the subfamilies Bryophilinae (Victrix acronictoides sp. n.) and Noctuinae, tribe Hadenini (Lacanobia chayu sp. n.) are described from China. Adults and male genitalia are illustrated. The checklists of the genera Victrix Staudinger, 1879 in China and Lacanobia Billberg, 1820 are presented.